Extraction techniques for phenolic compounds from Zingiber officinale: a review of traditional, microwave-assisted, and ultrasound-assisted methods - Febriani, Ni Kadek Dwi; Susanti, Ni Made Pitri; Dewi, Luh Putu Mirah Kusuma (Acta Pharmaciae Indonesia, 2025)
Background: The rhizome of Zingiber officinale (ginger) is widely recognized for its pharmacological properties, particularly its antioxidant activity, which is largely attributed to phenolic compounds such as gingerol, shogaol, paradol, and zingerone. Efficient extraction of these compounds requires suitable techniques to maximize yield while maintaining compound stability. Objective: This review aims to evaluate extraction techniques for phenolic compounds from ginger rhizomes, comparing traditional and modern approaches, and to identify methods that produce the highest total phenolic content (TPC). Methods: A literature review was conducted on original research articles published between 2015 and 2025 that reported phenolic extraction from Z. officinale using maceration, soxhlet extraction, reflux, microwave-assisted extraction (MAE), or ultrasound-assisted extraction (UAE). Articles were retrieved from Google Scholar and ScienceDirect databases and assessed against defined inclusion and exclusion criteria. Results: Six eligible studies were included, revealing substantial methodological heterogeneity that complicates direct method comparisons. UAE with 50% ethanol produced the highest TPC (155.19 ± 2.81 mg GAE/g dry weight), followed by Soxhlet extraction (31.10 ± 0.28 mg GAE/g) and MAE (27.89 ± 1.99 mg GAE/g). Reflux and maceration yielded comparatively lower TPC values, with results influenced by solvent type, concentration, temperature, and extraction time. Conclusion: UAE with 50% ethanol is the most effective technique for extracting phenolic compounds from ginger, offering both high yield and compound stability. MAE, while producing lower yields, remains advantageous for its shorter extraction duration.